FACTORS AFFECTING THE SOCIAL RESPONSIBILITY DISCLOSURE PRACTICE ON GO PUBLIC MANUFACTURING COMPANIES - Nurmala, Putri (Universitas Pamulang, 2018)
This study examines four factors that influence the practice of corporate social and environmental disclosure. The purpose of this study was to determine the effect of company size, type of industry, profitability, and family firm toward the practice of corporate social and environmental disclosure. This research is a quantitative study. The sample of these study are 48 go public manufacturing companies in Indonesia Stock Exchange that have announced annual reports for 2009 - 2013. From these samples that can be processed are 25 manufacturing companies that have announced annual reports for 2009 - 2013. Results of this study stated that the size of the company (net sales), type of industry, profitability (ROA), and family firm have significant positive effect on social and environmental disclosure practices of the company. Finally, through this research is expected that go public manufacturing companies can improve the practice of corporate social and environmental disclosures.